Personality and work behavior: Questioning the relevance of socially desirable responding - Galić, Zvonimir (2008)
Recent meta– analyses showed that personality traits are valid predictors of job performance in a wide range of professions. However, with an exception of some compound traits like integrity and in the cases when specific criteria are predicted, the established level of predictive validity is modest and probably underestimated. One of the reasons for relatively low validity coefficients could be found in the fact that personality questionnaires are subject to deliberate distortion. Many studies show that it is possible to distort responses to personality questionnaires in the desirable way when there is motivation to do so and that distortion is present in the context of personnel selection. However, because of the inconsistencies in research results, it is not quite clear to what extent is response distortion present in personnel selection context and what are its consequences for construct and predictive validity of personality traits and the quality of selection decisions. These doubts are even more complicated because of insufficient understanding of nature and methods for measurement of socially desirable responding. In this presentation, results of several studies dealing with response distortion on personality questionnaires and the nature of socially desirable responding will be shown. In the first part we will reexamine the extent to which response distortions on a personality questionnaire’ s scales are present in a personnel selection and show how they depend on the type of job candidates are applying for. The second part of discussion will deal with the nature of socially desirable responding and methods for its measurement. The results of two studies testing models of socially desirable responding that distinguish between deliberate impression management and unconscious self-deception will be presented. Finally, in the third part of the presentation summary discussion of obtained results, its implications for W/O psychology practice and plans for future studies will be given.